Women Empowerment Reinvented: Recognizing the Role of Religiosity in Gender Equality - Bhatta Joshi, Yashoda (Ganeshman Darpan, 2023)
Religious practices world-over play a significant role in shaping societies, cultures, and people’s beliefs and attitudes towards life. In Nepal, religion has been an integral part of the social fabric with women playing an active role in various religious practices. This paper mainly reflects the self-experience of ‘situated reality’ of Far-West Nepal by the author with the supportive literature from relevant sources. The discussion shows that women’s assertive presence at ‘religious space’ of their family and community has a positive impact on their social empowerment, enabling them to access resources, participate in decision making, and challenge gender-stereotypes. It has improved their self-confidence, enhanced their social status, and given them a sense of identity. Moreover, it has provided them a platform to activate their agency, build social capital, challenge patriarchal norms, and promote their rights. This paper concludes suggesting that women’s religious engagements can be a powerful means of achieving gender equality and their social empowerment.